2004
DOI: 10.1536/jhj.45.833
|View full text |Cite
|
Sign up to set email alerts
|

Tilt Training for Recurrent Neurocardiogenic Syncope: Effectiveness, Patient Compliance, and Scheduling the Frequency of Training Sessions

Abstract: SUMMARYUnsatisfactory results obtained with medical therapy and dual-chamber pacing for prevention of recurrent neurocardiogenic syncope necessitated the development of new treatment modalities. Tilt-training, a novel treatment for recurrent neurocardiogenic syncope based on exercise sessions with prolonged upright posture (either on a tilt-table or standing on foot against a wall), was shown to be effective in preventing the recurrence of neurocardiogenic syncope. The purpose of this study was to demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Our findings support the studies of Ector, Kinay, Reybrouck, and Di Girolamo (17, 18, 20, 21, 63), which habituated vasovagal syncope with static head-up tilt that would have activated otolith and body tilt receptors (23, 64). Habituation with head-up tilt takes significant time in the upright position and, therefore, would not involve the vertical semicircular canals.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings support the studies of Ector, Kinay, Reybrouck, and Di Girolamo (17, 18, 20, 21, 63), which habituated vasovagal syncope with static head-up tilt that would have activated otolith and body tilt receptors (23, 64). Habituation with head-up tilt takes significant time in the upright position and, therefore, would not involve the vertical semicircular canals.…”
Section: Discussionsupporting
confidence: 91%
“…An apparently promising therapy in which “syncope-sensitive” patients were repetitively tilted 60° for prolonged periods was originally shown to habituate the vestibulosympathetic reflex (VSR) and to reduce or abolish syncope (1721). These studies used repeated episodes of 60° static head-up tilt or standing against a wall for substantial periods of time that activated otolith and body tilt receptors (2224), both of which play a role in producing cardiovascular changes through the VSR in humans (2529).…”
Section: Introductionmentioning
confidence: 99%
“…This may be confirmed by the observations of the effectiveness of TT sessions performed only periodically. Repeated procedures associated with performing in-hospital and home training of prolonged standing may play a key role in gaining the ability of early identification of prodromal symptoms, which in turn helps preventing syncope in everyday life [9].…”
Section: Discussionmentioning
confidence: 99%
“…Other acute studies are less encouraging. Kinay et al [ 28 ] performed repetitive tilt training in 32 patients. They found that although 20 responded by the second session, three were resistant even after eight attempts.…”
Section: Tilt Trainingmentioning
confidence: 99%